Antigen-specific CTLs: to produce autologous cells product for adoptive cellular therapy. (June 2017) - Liu, Sai; Shao, Yi; Xu, Jie; Jiang, Na; Dai, Yanchao; Wang, Yu; Sun, Huanqing; Sun, Jianping; Zhang, Yonghong
Highlights: Major revision version Cell cultivation medium used in this research was serum free to ensure safety for further application in vivo; the result showed this medium could perfectly support the expansion of cells. Different cytokine environments were evaluated for their effect of supporting the expansion of cytotoxic lymphocyte expansion for both general and antigen-specific quantity. The method is capable to manufacture qualified cell product for in vivo cellular therapy, some profiles of the final product for each participant of the cellular therapy clinical trail is provided. Minor revision version: Implement of reference is done to prove the peptide specific CTLs recognize naturally processed and represented antigen. Table 1 is divided into 2 tables to make it more convenient and streamlined. Abstract: As antiretroviral therapy provides long term viral suppression but no cure, alternative therapies such as adoptive cellular therapy have thus been investigated in the anti-AIDS field. Objective: This study sought to establish a HLA-A02 specific CTL cell culture method with comparison of the effects of different cytokines used in CTL cultivation to decide the best cultivation environment. In order to produce CTLs with targeted HLA-A02 restricted antigen specificity for adoptive cellular therapy, we evaluated autologous PBMC cultivation in different cytokine environment to select a better expansion condition to produce qualified CTL production. Methods: We co-cultivated PBMC and peptides of these patients with HLA-A02 allele with different cytokines. After cultivation, multiple parameters were tested. Results: 1) Cytokines IL-2 alone can effectively amplify HLA-A02 specific CTL cells, and the count of CTLs was > 85% all through the process. 2) The HLA-A02 specific cells at the end of the cultivation were mainly CD3 + CD8+ cells. 3) The interferon stimulation test had shown that the expanded CTLs secreted more IFN-γ than before cultivation (0.9% -11.70%). Conclusion: This model of CTL cultivation is successful in redirecting the specificity of antigen recognition and safely for HLA-A02+ patients cell adoptive therapy.